Hubungan Antara Kecemasan Dengan Kualitas Tidur Pada Mahasiswa yang Mengalami Stres Akademik - Fadhila Khoirunnisa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Sleep quality is an essential aspect of individuals' physical and psychological well-being. University students are among the groups most vulnerable to sleep quality problems due to academic demands that may induce stress and anxiety. This study aimed to examine the relationship between anxiety and sleep quality among students experiencing academic stress. A quantitative correlational design was employed involving 120 students from Bhayangkara University, Greater Jakarta, selected using incidental sampling. Data were collected using the Insomnia Severity Index (ISI) to assess sleep quality and an adapted version of the State–Trait Anxiety Inventory (STAI) to measure anxiety. Data were analyzed using Spearman's rank correlation. The results revealed a significant positive correlation between anxiety and sleep quality (r = 0.814, p 0.001), indicating a very strong association. Higher levels of anxiety were associated with poorer sleep quality among students experiencing academic stress. These results suggest that anxiety is significantly associated with sleep quality in students experiencing academic stress.